Sinusoidal changes in transcutaneous oxygen pressure, suggesting Cheyne-Stokes respiration, are frequent and of poor prognosis among patients with suspected critical limb ischemia. (January 2021) - Hersant, Jeanne; Ramondou, Pierre; Trzepizur, Wojciech; Gagnadoux, Frederic; Picquet, Jean; Abraham, Pierre; Henni, Samir
Abstract: Background and aims: Transcutaneous oxygen pressure (TcpO2 ) is used in patients with suspected critical limb ischemia (CLI). Sinusoidal changes (SC ) in TcpO2 are found in patients with Cheyne-Stokes respiration (CSR). We aimed to determine the characteristics of TcpO2 changes at rest in patients with suspected CLI, define the objective criteria for SC TcpO2 patterns (SC+), and estimate the prevalence of SC+ in our population and its impact on the outcome. Methods: We retrospectively analyzed 300 chest TcpO2 recordings performed in a 16-month period. We determined the presence/absence of SC TcpO2 by visual analysis. We determined the acceptable error in the regularity of peaks of the cross-correlation with ROC curve analysis, among patients with typical SC TcpO2 and non-sinusoidal patterns. Then, we defined SC + as a minimum of five peaks, a standard deviation of TcpO2 >1.25 mmHg, an error in regularity of peaks of the cross-correlation < 10%, and a cycle length between 30 and 100 s. In patients included until October 2019, we compared the outcome as a function of SC + or SC- with Cox models. Results: Mathematical detection of SC + found that 43 patients (14.3%) fulfilled all four defined criteria at the chest level, but only 23 did so at the limb level. In the follow-up of 207 patients, the presence of Sc TcpO2 at the chest significantly increased the risk of mortality: hazard ratio: 2.69 [95%CI: 1.37–5.30]; p < 0.005. Conclusions: SC TcpO2 is frequent, and is associated with a poor outcome in patients with suspected CLI. Graphical abstract: Image 1 Highlights: Critical limb ischemia (CLI) conveys a high risk of morbidity and mortality. Transcutaneous oxygen pressure (TcpO2 ) at rest is used in CLI-suspected patients. Cheyne-Stokes respiration (CSR) induces sinusoidal (SC) oscillations of TcpO2 . We found a 14.3% prevalence of chest SC-TcpO2 in 300 patients with suspected CLI. The presence of chest SC-TcpO2 was associated with an increased risk of mortality.